The Effect of The Quality of Disclosure And The Fair Value of Biological Assets On Company Value - Vebry Resky Aulia Domo; Wiwik Utami (Dinasti Publisher, 2022)
The research purpose to examines or analyzes the impact of disclosure quality and fair value of biological assets on company valuation (Tobins Q) on the Indonesian Agriculture Industry. The control variables in this journal are the Return on Assets (ROA) and Debt to Assets (DAR) variables. The sample of this study is 13 of the total 19 population of agricultural companies in the period 2018 to 2020 which are listed on the Indonesian stock exchange. The multiple regression analysis method used in this study informs that the quality of disclosure of biological assets has no significant positive effect on firm value. While the valuation of biological assets using the fair value method has a significant positive effect on firm value.